Family Communication As a Medium For Delivering Moral Messages In Just Mom Film - Ryan Habil Utama; Vani Dias Adiprabowo; Wahyuni Lestari; Fajar Dwi Putra Dwipa (Fakultas Ekonomi dan Ilmu Sosial Program Studi Ilmu Komunikasi Universitas AMIKOM Yogyakarta, 2023)
This study aims to find out about the family communication pattern used in the just mom film in conveying a moral message to the audience and how family communication occurs in the just mom film to create effective communication and create family harmony. This type of research is basic research using qualitative descriptive methods and content analysis approaches and interpretive paradigms to see patterns of communication that occur using family communication as the object of research. This study uses two data collection techniques, namely observation, and documentation which will be processed to obtain appropriate and accurate data. The analysis technique used is a qualitative content analysis technique that is useful for finding, identifying, processing, and analyzing several dialogues that contain moral messages in several scenes of the Just Mom film, to then see the pattern of communication. The findings from this study indicate that the family communication pattern that was formed in this just-mom film is the Permissive communication pattern. The permissive communication pattern itself is the communication pattern of parents who tend to free their children more to do whatever they want. Meanwhile, the moral message to be conveyed in the film Just Mom has been successfully conveyed to the audience through interpersonal communication and family communication patterns shown by the role of parents to their children. The findings from this study indicate that the family communication pattern that was formed in this just-mom film is the Permissive communication pattern. The permissive communication pattern itself is the communication pattern of parents who tend to free their children more to do whatever they want. Meanwhile, the moral message to be conveyed in the film Just Mom has been successfully conveyed to the audience through interpersonal communication and family communication patterns shown by the role of parents to their children. The findings from this study indicate that the family communication pattern that was formed in this just-mom film is the Permissive communication pattern. The permissive communication pattern itself is the communication pattern of parents who tend to free their children more to do whatever they want. Meanwhile, the moral message to be conveyed in the film Just Mom has been successfully conveyed to the audience through interpersonal communication and family communication patterns shown by the role of parents to their children.